2016
DOI: 10.4084/mjhid.2017.009
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Lymphoma: The Management of Elderly Patient

Abstract: Follicular lymphoma (FL) is the most common indolent non-Hodgkin lymphoma, which typically affects mature adults and elderly, whose median age at diagnosis is 65 years. The natural history of FL appears to have been favorably impacted by the introduction of Rituximab. Randomized clinical trials demonstrated that the addition of rituximab to standard chemotherapy induction has improved the overall survival and new strategies of chemo-immunotherapy, such as Bendamustine combined with Rituximab, showed optimal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…However, nearly a third of patients with FL will suffer histologic transformation into a high-grade lymphoma often termed transformed FL (tFL), that is morphologically indistinguishable from DLBCL, with a much worse prognosis than the antecedent FL. 147,148 We identified a signature of 6 miRNAs ( miR-223, miR-217, miR-222, miR-221 , and let-7i and let-7b ) that could distinguish between de novo DLBCL and tFL. 50 Subsequently, miR-31 and miR-17-5p have also been identified as being differentially expressed between FL and tFL.…”
Section: Aberrant Expression Of Mirnas In B-cell Lymphomamentioning
confidence: 99%
“…However, nearly a third of patients with FL will suffer histologic transformation into a high-grade lymphoma often termed transformed FL (tFL), that is morphologically indistinguishable from DLBCL, with a much worse prognosis than the antecedent FL. 147,148 We identified a signature of 6 miRNAs ( miR-223, miR-217, miR-222, miR-221 , and let-7i and let-7b ) that could distinguish between de novo DLBCL and tFL. 50 Subsequently, miR-31 and miR-17-5p have also been identified as being differentially expressed between FL and tFL.…”
Section: Aberrant Expression Of Mirnas In B-cell Lymphomamentioning
confidence: 99%
“…BCL2 and EZH2 genes are both key genes in the pathogenesis of FL [ 20 , 26 , 27 ]. The t(14;18) translocation, present in >85% of FL cases, is considered the molecular hallmark of this disease and results in constitutive expression of the antiapoptotic protein BCL2 [ 28 , 29 , 30 ]. We observed that mutations in the BCL2 3´ UTR binding site for miR-5008 decreased the downregulation of this gene, thereby increasing BCL2 expression in luciferase assays, although we were not able to confirm this phenomenon in FL18 or U2932 cells, probably due to high basal levels of BCL2 expression in these t(14;18) cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Half of all FL patients are 60 or above, and treatment choices in these groups can be more difficult due to overall health and comorbidities. Still, the low toxic side effects of rituximab compared with chemotherapies indicate mAb as a safe and effective treatment in elderly FL patients both in combination or often as a monotherapy ( 47 ).…”
Section: Clinical Impact Of Rituximab In B-cell Nhl Treatmentmentioning
confidence: 99%